The concept of life and the genesis of the human order - Ramos, Silvana de Souza (Cadernos Espinosanos, 2009)
This paper investigates the transition from nature to culture through the concept of life, taking as basis the Bergson, Canguilhem and Merleau-Ponty’s formulations. In order to do that, it is necessary to investigate the genesis of modes of subjectivation – the vital action, the organism’s normativity and the expressive character of life – stated by each one of the authors, so that we can reflect on up to which point one can explain the human order (that is, the history and the culture) through its linking to the nature.